Pelatihan Penggunaan Pelabelan Lanskap Linguistik Pariwisata bagi Pemandu Wisata Keraton Kasepuhan Cirebon - Syafroni, Roni Nugraha (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Labeling activities at the Keraton Kasepuhan Cirebon were carried out using the theory of linguistic tourism landscapes. There are six labels documented using a digital camera. This training is necessary because the Cirebon Kasepuhan Palace is a tourist attraction that is frequently visited by domestic and foreign tourists, so labeling in the palace environment must also accommodate the needs of all tourists through the language used on the label. Then, training activities were carried out for tour guides on the six labels. This training aims to introduce tourism linguistic landscape theory to tour guides. The method used in implementing this PKM program is the mentoring or PAR (Participatory Action Research) method. Then data collection was carried out with a site survey and documentation of materials for training and discussion. The training steps are preliminary, implementation, and evaluation steps. The results and conclusions of this dedication are that linguistics can be useful to be juxtaposed with other sciences and be useful for the knowledge of the wider community. This training can also help tour guides explain more clearly to tourists when explaining objects in the palace environment through brand information.